Application of Plant Extracts in Micropropagation and Cryopreservation of Bleeding Heart: An Ornamental-Medicinal Plant Species - Dariusz Kulus; Natalia Miler (Agriculture, 2021)
Lamprocapnos spectabilis (L.) Fukuhara (bleeding heart) is valued both in the horticultural and pharmaceutical markets. Despite its great popularity, information on the in vitro tissue culture technology in this species is limited. There is also little knowledge on the application of plant extracts in the tissue culture systems of plants other than orchids. The aim of this study is to compare the utility of traditional plant growth regulators (PGRs) and natural extracts—obtained from the coconut shreds, as well as oat, rice, and sesame seeds—in the micropropagation and cryopreservation of L. spectabilis ‘Gold Heart’ and ‘White Gold’. The biochemical analysis of extracts composition is also included. In the first experiment related to micropropagation via axillary buds activation, the single-node explants were cultured for a 10-week-long propagation cycle in the modified Murashige and Skoog medium fortified either with 1.11 µM benzyladenine (BA) and 1.23 µM indole-3-butritic acid (IBA) or with 10% (v/v) plant extracts. A PGRs- and extract-free control was also considered. In the cryopreservation experiment, the same 10% (v/v) extracts were added into the medium during a seven-day preculture in the encapsulation-vitrification cryopreservation protocol. It was found that the impact of natural additives was cultivar- and trait-specific. In the first experiment, the addition of coconut extract favoured the proliferation of shoots and propagation ratio in bleeding heart ‘Gold Heart’. Rice extract, on the other hand, promoted callus formation in ‘White Gold’ cultivar and was more effective in increasing the propagation ratio in this cultivar than the conventional plant growth regulators (4.1 and 2.6, respectively). Sesame extract suppressed the development of the explants in both cultivars analysed, probably due to the high content of polyphenols. As for the second experiment, the addition of plant extracts into the preculture medium did not increase the survival level of the cryopreserved shoot tips (sesame and oat extracts even decreased this parameter). On the other hand, coconut extract, abundant in simple sugars and endogenous cytokinins, stimulated a more intensive proliferation and growth of shoots after rewarming of samples. Analysing the synergistic effect of conventional plant growth regulators and natural extracts should be considered in future studies related to L. spectabilis.